Information acquisition in an experimental asset market - M. Middeldorp; Stephanie Rosenkranz (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2008)
We use experimental evidence from a complex trading environment to evaluate the rational expectations theory of information acquisition in an asset market. Although theoretical predictions correctly identify the main drivers of information acquisition in our experimental data, we observe much higher levels of information acquisition. Our evidence suggests that this comes about because the theory overstates the informativeness of trading and thus predicts that few agents will want to buy information. We use indicators such as trading volume to confirm that information acquisition is sensitive to the informativeness of trading. We also test three other theories presented in recent models in the tradition of the rational expectations approach. We find some confirmation that subjects have a strategic incentive to increase their own acquisition in reaction to the acquisition of others. On the other hand, we find no indications of wealth effects or overconfidence in our experimental setup. Overall our evidence suggests that more realistic assumptions, particularly about the informativeness of trading, are needed to accurately predict the levels of information acquisition.
Keywords: 330; Information and Financial Market Efficiency; Private Information Acquisition; Experimental Economics